Technonationalist trends in the development of global actors of military innovation - Skliar, Nadiia (Social Development and Security, 2021)
The article is devoted to the study of the theory and practice of one of the schools of management of national competitiveness – techno-nationalism. The aim of the study is to identify the features of the development of modern techno-nationalism, the practices of managing national competitiveness in the defense industry sector of the countries of the world technological core, and to identify potential threats to the impact of the implementation of such a policy on the global and national security of other countries.The specific characteristics of modern technologies associated with dual-use are considered. The rating position of the leading countries in terms of technologies by sectors of the economy has been investigated, with the definition of the features of techno-nationalist policies of European and Asian countries. The fundamental ideological differences between the two systems are indicated. The current innovative technology trends associated with dual-use technologies in the United States and China have been identified. The increasing influence of the American government on other markets for the latest technologies in the countries of the world has been proven.The guidelines of Beijing's techno-national policy towards new quantum computing (QC) are considered, which determines not only an increase in the country's military-technological potential but also possible future challenges on a global and regional scale. The technological trends in the development of innovative technologies that cause concern of the world community and can be the basis for the formation of national and global risks and threats to security have been identified.